2020
DOI: 10.1038/s41467-019-14073-6
|View full text |Cite
|
Sign up to set email alerts
|

Circular photogalvanic spectroscopy of Rashba splitting in 2D hybrid organic–inorganic perovskite multiple quantum wells

Abstract: The two-dimensional (2D) Ruddlesden−Popper organic-inorganic halide perovskites such as (2D)-phenethylammonium lead iodide (2D-PEPI) have layered structure that resembles multiple quantum wells (MQW). The heavy atoms in 2D-PEPI contribute a large spin-orbit coupling that influences the electronic band structure. Upon breaking the inversion symmetry, a spin splitting ('Rashba splitting') occurs in the electronic bands. We have studied the spin splitting in 2D-PEPI single crystals using the circular photogalvani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
112
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(116 citation statements)
references
References 48 publications
4
112
0
Order By: Relevance
“…The predicted of 1.52 eV·Å and estimated ( ) 32 , 49 of 55 meV in chiral NPB are orders of magnitude higher than those found in QW heterostructures such as InAlAs/InGaAs ( eV·Å; meV) 50 . These values are indeed similar to those recently observed in the 2D phenethylammonium lead iodide HOIP using optical spectroscopies 36 , 49 , although the precise origin of the bulk inversion asymmetry is still unclear given its centrosymmetric X-ray crystal structure with a symmetrical disposition of in-plane bond angles and relatively low distortions (in contrast to chiral NPB) 26 . We speculate that an instantaneous band splitting in phenethylammonium lead iodide can arise from dynamic structural changes induced by temperature and/or photoexcited coherent phonon modes, as recently proposed for methylammonium lead iodide 3D perovskite 51 , 52 .…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The predicted of 1.52 eV·Å and estimated ( ) 32 , 49 of 55 meV in chiral NPB are orders of magnitude higher than those found in QW heterostructures such as InAlAs/InGaAs ( eV·Å; meV) 50 . These values are indeed similar to those recently observed in the 2D phenethylammonium lead iodide HOIP using optical spectroscopies 36 , 49 , although the precise origin of the bulk inversion asymmetry is still unclear given its centrosymmetric X-ray crystal structure with a symmetrical disposition of in-plane bond angles and relatively low distortions (in contrast to chiral NPB) 26 . We speculate that an instantaneous band splitting in phenethylammonium lead iodide can arise from dynamic structural changes induced by temperature and/or photoexcited coherent phonon modes, as recently proposed for methylammonium lead iodide 3D perovskite 51 , 52 .…”
Section: Resultssupporting
confidence: 86%
“…Opposite spin textures associated with the spin-split sub-bands in opposite momentum directions (Fig. 3b ) due to the RD SOC effect lead to circular photogalvanic effects 36 and enable interconversion between charge and spin currents (by Edelstein and inverse Edelstein effects) 22 , 23 , of interest for spintronic technologies.…”
Section: Resultsmentioning
confidence: 99%
“…Using available measured values for the exchange and Rashba parameters determined experimentally in lead-iodide based 2D HOIS systems 35,36,46,47 , we showed that CD on the order of 10% for spectrally resolved fine structure transitions can occur for top illumination conditions in orthorhombic perovskites with inversion symmetry breaking normal to the 2D layers. For optimal side illumination conditions, spectrally resolved exciton fine structure levels may exhibit CD approaching 100%.…”
Section: Discussionmentioning
confidence: 95%
“…Since many perovskites adopt an orthorhombic crystal structure at low temperature, we consider an orthorhombic system with inversion symmetry breaking normal to the surface along a two-fold rotation axis: The structure possesses non-chiral C 2v point symmetry (see Figure 1) and is expected to exhibit spin splitting due to the large spin orbit coupling in these systems. Calculations of excitonic light absorption conducted in quasi-two dimensional metal halide perovskites using experimentally determined Rashba spin-orbital splitting parameters 35,36 show CD with an anisotropy factor 14 of up to 30%.…”
mentioning
confidence: 99%
“…Recent work shows that layered RPP crystals can be exfoliated to yield flakes that are as thin as a single quantum well on account of the weak intermolecular van der Waals interactions between the organic chains 18 . The multiple quantum well structure of RPP presents thickness-controllable tunneling barriers, and the strong spin-orbit coupling (SOC) imbued in Pb, combined with a symmetry-breaking field in the direction perpendicular to the 2D surface, may generate Rashba spin-split bands, thus presenting the prospect for applications in spin-optoelectronics 19 , 20 . Compared to bulk crystals, molecularly thin perovskites offer better gate dielectrics and conformal adhesion on electrodes, thus mitigating the contact barrier issues faced by thicker crystals 18 , 21 .…”
Section: Introductionmentioning
confidence: 99%